2008
DOI: 10.1177/175114370800900121
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Insulin Therapy and Pentastarch Resuscitation in Severe Sepsis

Abstract: Neither intensive insulin therapy nor the use of pentastarch as the resuscitation fluid reduces 28-day mortality or morbidity from severe sepsis. Intensive insulin therapy may cause harm because of increased hypoglycaemic episodes. Use of pentastarch increases the need for renal replacement therapy. Level of evidence: 1+ (RCT with a low risk of bias)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Several large-size trials have investigated the optimal acute blood glucose control in critically ill patients, including septic ones [22,[45][46][47]. However, only a few small studies were restricted to septic patients [48,49], and none specifically targeted diabetic patients. Table 1 reports the main clinical trials evaluating the impact of different targets of acute glycemic control in critically ill and septic patients.…”
Section: Optimal Blood Glucose Control During Sepsismentioning
confidence: 99%
See 1 more Smart Citation
“…Several large-size trials have investigated the optimal acute blood glucose control in critically ill patients, including septic ones [22,[45][46][47]. However, only a few small studies were restricted to septic patients [48,49], and none specifically targeted diabetic patients. Table 1 reports the main clinical trials evaluating the impact of different targets of acute glycemic control in critically ill and septic patients.…”
Section: Optimal Blood Glucose Control During Sepsismentioning
confidence: 99%
“…However, further studies failed to confirm these benefits from TGC [22,[46][47][48], although differences in study design, selection of patients, nutritional support, targeted glucose range and blood glucose measurements make the comparison challenging [41]. As a matter of fact, a further trial specifically involving patients with severe sepsis [48] not only failed to demonstrate a benefit on mortality from TGC, in both diabetic and non-diabetic patients, but was early stopped for safety reasons (e.g., a significantly increased rate of severe hypoglycemic events). Two further large-scale trials including mixed populations of medical and surgical patients, the Glucontrol study [47] and the Normoglycemia in Intensive Care Evaluation-Survival Using Glucose Algorithm Regulation (NICE-SUGAR) Trial [22], reported higher rates of hypoglycemia in the TGC group.…”
Section: Optimal Blood Glucose Control During Sepsismentioning
confidence: 99%